VanGrack's Explanations: Treating the Truth As a Mere Matter of “Form” - Jeffrey Fagan; James S. Liebman; Valerie West (Washington University Law Quarterly, 2002)
The inaccuracies in Adam VanGrack’s Note, and new problems with his present explanation, lead us to conclude that it is not useful to exchange views with him in the Washington University Law Quarterly. Beyond all is Mr VanGrack’s dismissal of matters serious enough to trigger an extraordinary instruction to explain himself in print, and to prompt him to rescind statements published only a few months ago, as mere “semantic complaints.” This reply seeks to discuss the authors' data-sharing arrangements.
Keywords: Social sciences; Peer review (Professional performance); Law -- Periodicals; Capital punishment